2003
DOI: 10.1056/nejmoa022170
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin-Induced Correction of CFTR Function in Patients with Cystic Fibrosis andCFTRStop Mutations

Abstract: In patients with cystic fibrosis who have premature stop codons, gentamicin can cause translational "read through," resulting in the expression of full-length CFTR protein at the apical cell membrane, and thus can correct the typical electrophysiological abnormalities caused by CFTR dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
335
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(344 citation statements)
references
References 24 publications
0
335
2
6
Order By: Relevance
“…This is being critically evaluated for cystic fibrosis (13)(14)(15)(16) and muscular dystrophy (17)(18)(19)(20)(21)(22). After animal studies, gentamicin-induced CFTR protein was recently reported to improve transmembrane conductance across the nasal mucosa in a group of 10 patients with homozygous PTC mutations in the CTRF gene; patients with the more common del508F mutation were used as controls and showed no improvement of conductance (16). Studies treating mdx mice with gentamicin were reported to restore dystrophin function in skeletal muscle (17).…”
Section: Discussionmentioning
confidence: 99%
“…This is being critically evaluated for cystic fibrosis (13)(14)(15)(16) and muscular dystrophy (17)(18)(19)(20)(21)(22). After animal studies, gentamicin-induced CFTR protein was recently reported to improve transmembrane conductance across the nasal mucosa in a group of 10 patients with homozygous PTC mutations in the CTRF gene; patients with the more common del508F mutation were used as controls and showed no improvement of conductance (16). Studies treating mdx mice with gentamicin were reported to restore dystrophin function in skeletal muscle (17).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of NMD has led to efforts to develop therapeutic agents that modulate this process, especially whereby suppression of a disease-related mutation that normally triggers NMD permits translation read-through and partial restoration of critical protein products (24,25). NMD also plays an important role in the posttranscriptional regulation of numerous RNA binding and processing factors (14,15,18,26).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 19 CF patients were either homozygous (n511) or heterozygous (n58) for CFTR stop mutations and a total of five patients were homozygous for the Class II mutation F508del [39]. Gentamicin was shown to significantly reduce the nasal potential difference (a measure of CFTR function) in those patients with stop mutations (from basal potential difference 45¡8 to 34¡11 mV, p50.005), whereas no significant difference was seen in patients homozygous for F508del [39]. Positive effects were also demonstrated by SERMET-GAUDELUS et al [40], although no effect was noted in another study [41].…”
Section: Cftr Modulatorsmentioning
confidence: 99%